Performance As Seen From Workload And Motivation At Perumdam Tirta Yapono Ambon City - Felix Chandra (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
This research was conducted to determine the influence and magnitude of workload on motivation and performance, motivation on performance and the influence of motivation as a mediator of workload on performance. This research is a quantitative methods. This research was conducted at Perumdam Tirta Yapono, Ambon City. The population in this study was employees of Perumdam Tirta Yapono with a total of 101 employees. The number of samples in this study was 50 employees, determined using the Slovin formula and simple random sampling technique. The measurement scale used is the Likert scale. The data in this research was collected by distributing questionnaires to respondents. Path analysis is a data analysis technique used to test hypotheses. Data from the questionnaire was processed with the help of SPSS tools. The results of this research show that workload has a positive and significant effect on motivation, motivation has a positive and significant effect on performance, workload has a positive and significant effect on performance and motivation does not mediate the effect of workload on performance.